ANALISIS KOEFISIEN KERUGIAN PADA PERCABANGAN PIPA - Rachmat Subagyo (INFO-TEKNIK, 2009)
As long as the liquid flows through the piping installation system, many losses of pressure called major loss of pressure and minor loss of pressure (a loss due to the fluid passes a branch). The distribution of liquid flow in the branch is an irreversible process in which this irreversibility will degrade the performance system. The way to discover the loss occurs at the pipe branching is by measuring the coefficient of loss. The type of experiment conducted was by making three branches of galvanic pipes of medium size with the angles 450, 600 and 900 with the variation of Re from 0 to 5,5 x 104.The result of branch K32 study is K32(45) =K32(60)=K32(90)= (0,07-0,39), branch K31: K31(45)= (0,95-0,60), K31(60)=(1,08-0,85) and K31(90)=(1,01-1,50). The total coefficient of loss is Ktot(45)= (1,02-0,97), Ktot(60)=(1,15-1,23) and Ktot(90)=(1,17-1,89).